Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1472-6882-13-192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cocktail of four local Malaysian medicinal plants (Phyllanthus spp.) against dengue virus 2

Abstract: BackgroundThe absence of commercialized vaccines and antiviral agents against dengue has made the disease a major health concern around the world. With the current dengue virus transmission rate and incidences, the development of antiviral drugs is of vital need. The aim of this project was to evaluate the possibility of developing a local medicinal plant, Phyllanthus as an anti-dengue agent.MethodsCocktail (aqueous and methanolic) extracts were prepared from four species of Phyllanthus (P.amarus, P.niruri, P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 47 publications
1
34
1
1
Order By: Relevance
“…Natural products have been considered as an important alternative to manage several diseases, such as dengue (Rothan et al, 2014; Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products have been considered as an important alternative to manage several diseases, such as dengue (Rothan et al, 2014; Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As authors have demonstrated the antiviral effect of medicinal plants against DENV (Tang et al, 2012; Lee et al, 2013;Rothan et al, 2014), the aim of this study was to review systematically the published research concerning the use of medicinal plants in the management of dengue using the PubMed database. Considering the findings described in the literature, it is hypothesized an antiviral activity against DENV of some medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to vaccines, every other possible treatment including alternative medicines are being investigated to test their usefulness in controlling this problem. Lee and his co-investigators demonstrated the effectiveness of cocktail extracts prepared from four species of phyllanthus against the DENV [9].…”
Section: Brief Review Of Dengue Fevermentioning
confidence: 99%
“…The maximum non-toxic dose on Vero cells for both aqueous and methanolic extracts were determined to be 250μg/ml and 15.63μg/ml respectively. At these concentrations, Phyllanthus showed strongest inhibitory activity against DENV2 with more than 90% of virus reduction in simultaneous treatment through regulation of various proteins that play important roles in cell-virus attachment, viral entry, viral polyprotein production, viral RNA replication as well as viral assembly and maturation (17,37). Inhibition of the viral entry into the host cell via binding of viral E protein to heparin sulfate during early infection is normally the first point of intervention (34).…”
Section: Antiviral Activity Of Phyllanthusmentioning
confidence: 99%
“…Herpesviridae family consists of at least eight species of single large double stranded DNA enveloped viruses that are pathogenic to humans (16)(17)(18)(19)(20). Among these species, HSV-1 and HSV-2 are more intriguing due to the enormous clinical symptoms that they may manifest, ranging from gingivostomatitis to keratoconjunctivitis, genital disease, encephalitis.…”
Section: Introduction On Hsvmentioning
confidence: 99%